2015
DOI: 10.1111/cge.12571
|View full text |Cite
|
Sign up to set email alerts
|

Dysmorphology services: a snapshot of current practices and a vision for the future

Abstract: Dysmorphology concerns the recognition and management of rare, multiple anomaly syndromes. Genomic technologies and software for gestalt recognition will re-shape dysmorphology services. In order to reflect on a model of the service in the post-genomic era, we compared the utility of dysmorphology consultations in two Mediterranean cities, Athens, Greece and Afula, Israel (MDS), the Manchester Centre for Genomic Medicine, a UK service with dysmorphology expertise (UKDS) and the DYSCERNE, digital service (DDS).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
0
3
0
1
Order By: Relevance
“…Dysmorphology workshops and courses have been a mainstay of the ESHG portfolio (Donnai, 2017). These have been crucial in educating professionals in a field which is integral to the care of patients and families with rare inherited developmental disorders (Douzgou et al, 2016a). The interactive forum created by the dysmorphology courses forged an environment from which the Young Geneticists' Network and the European Society of Human Genetic-Young Committee (ESHG-Y) were founded.…”
Section: Educational Coursesmentioning
confidence: 99%
“…Dysmorphology workshops and courses have been a mainstay of the ESHG portfolio (Donnai, 2017). These have been crucial in educating professionals in a field which is integral to the care of patients and families with rare inherited developmental disorders (Douzgou et al, 2016a). The interactive forum created by the dysmorphology courses forged an environment from which the Young Geneticists' Network and the European Society of Human Genetic-Young Committee (ESHG-Y) were founded.…”
Section: Educational Coursesmentioning
confidence: 99%
“…Centres of Expertise for Dysmorphology have been established in some countries within the EU [16]. The diagnostic yield of a dysmorphology service is variable, and a delayed or uncertain diagnosis has been reported as 38% because of the rarity of many of the conditions, the uneven distribution or availability of dysmorphology services resulting in unequal access to specialists and the different experience, training and aptitude of the dysmorphologists concerned [17,18]. …”
Section: Identification Of Clinical Genetic Service Need/crowdsourcinmentioning
confidence: 99%
“…We previously described our experience of using a web-based process to facilitate access to a specialised clinical genetics service [8]. We showed that sharing patient medical records for expert review can lead to new diagnoses, the delineation of new gene-disease correlations, advice on clinical management and education of the participating experts [8][9][10].…”
Section: Introductionmentioning
confidence: 99%